Use of the tumor-infiltrating CD8 to FOXP3 lymphocyte ratio in predicting treatment responses to combination therapy with pertuzumab, trastuzumab, and docetaxel for advanced HER2-positive breast cancer - Takada, Koji (J Transl Med, 2018)
BACKGROUND: The trastuzumab, pertuzumab, and docetaxel (TPD) regimen is strongly recommended as a treatment option for first-line therapy for advanced human epidermal growth factor receptor (HER) 2-positive breast cancer. Monitoring the host microenvironments in cancer plays a significant role in predicting prognoses and curative effects. It is important to clarify the role of immune related gene expression in tumor-infiltrating lymphocytes in the tumor microenvironment. In this study, we evaluated the impact of chemotherapy with a TPD regimen, on immune micro environments in HER2-positive breast cancer using immune related proteins as indicators. METHODS: The subjects consisted of 30 patients who received the TPD regimen. The expression levels of estrogen receptor, progesterone receptor, Ki67, CD8, forkhead box protein (FOXP) 3, programmed death (PD) 1, programmed death ligand (PD-L) 1, CD163, phosphatase and tensin homolog and lymphocyte activation gene 3 were evaluated in biopsy specimens, by immunostaining. RESULTS: CD8(+), CD8/FOXP3 ratio (CFR)(high) and PD-L1(−) group had significantly longer PFS than the CD8(−), CFR(low) and PDL1(+) group (p = 0.045, log-rank) (p = 0.007, log-rank) (p = 0.040, log-rank), respectively. The CFR(high) group had significantly better OS than the CFR(low) group (p = 0.034, log-rank). In the univariate analysis, CD8(+), CFR(high) groups extended PFS significantly (p = 0.027, hazard ratio [HR] = 0.162) (p = 0.008, HR = 0.195), respectively. The receiver operating characteristic (ROC) analyses showed that the results for CFR [area under the curve (AUC): 0.708] were better than those for other factors (AUC: CD8 = 0.681, FOXP3 = 0.639, PD1 = 0.528, PD-L1 = 0.681). CONCLUSIONS: This study shows with the TPD regimen, a high CFR leads to a high ORR and long PFS in HER2-positive breast cancer. CFR, therefore, may be one of the important prognostic factors for this disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12967-018-1460-4) contains supplementary material, which is available to authorized users.